2019
DOI: 10.1080/16549716.2019.1685808
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of an economic support component to reduce early pregnancy and school dropout in Zambia: a qualitative case study

Abstract: Background: Cash Transfer (CT) schemes have become popular poverty reducing measures in many low and middle-income countries. Research indicates that when provided to girls in resource poor settings, cash transfers can increase education and postpone marriage and pregnancy. However, a few studies indicate that they can also have negative effects which can affect their acceptability, such as generating intra-community tensions.Objective: Conceptually informed by Rogers’ diffusion of innovation theory, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…While our inclusion criteria focused on primary acceptability research with adolescents and young adults, it should be noted that 25 studies also collected acceptability data from other stakeholders. These include caregivers or other family members, 32–40 teachers, facilitators, 26 41 42 community leaders or gate keepers, 28 43 peer mentors, service providers and healthcare workers. 44–51 Since the focus of this mapping review is the acceptability of young adults specifically, we do not synthesise or report on perspectives of other stakeholders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While our inclusion criteria focused on primary acceptability research with adolescents and young adults, it should be noted that 25 studies also collected acceptability data from other stakeholders. These include caregivers or other family members, 32–40 teachers, facilitators, 26 41 42 community leaders or gate keepers, 28 43 peer mentors, service providers and healthcare workers. 44–51 Since the focus of this mapping review is the acceptability of young adults specifically, we do not synthesise or report on perspectives of other stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for acceptability of economic support interventions included financial autonomy 78 and the freedom to decide how to use cash transfers. 28 However, concerns around the process of selecting which individuals or households were to receive transfers, as well as inclusion, sustainability and effects on social relations and social equity within the community, 38 78 were factors that threatened acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…To be as inclusive as possible, we included 10 studies that did not clearly specify the exact age range of participants, but for which available information indicated that the sample would have been entirely or almost entirely within this range (e.g. secondary school and university students (23-28) 0r where sample descriptive data indicated a sample consisting almost entirely of participants 24 or younger (29-31).…”
Section: Resultsmentioning
confidence: 99%
“…While our inclusion criteria focused on primary acceptability research with adolescents and young adults, it should be noted that 25 studies also collected acceptability data from other stakeholders. These include caregivers or other family members (32-40), teachers, facilitators (26, 41, 42), community leaders or gate keepers, (28, 43), peer mentors, service providers and healthcare workers (29, 44-51).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation